Integration of Entrepreneurship Education With Biology Education Study Program Courses: Student Perceptions - Husni, Rafeah; Nasution, Yusnita Anwar (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to explore biology education students' perceptions of integrating entrepreneurship education with courses, interest in entrepreneurship, and self-efficacy. This study is an exploratory descriptive research, the respondents were 77 biology education students at UIN SYAHADA Padangsidimpuan. The instrument used was a closed questionnaire with the Guttman scale. Research data was analyzed descriptively and inferential statistics using the Kruskal Wallis test. The results of the study are: 1) student perceptions regarding the integration of entrepreneurship education are very positive, as many as 83.1% of students feel that integration needs to be implemented. Based on the Sig value (0.86 0.05), there is no significant difference between the perceptions of semester III, V, and VII students; 2) Students' entrepreneurial interest is relatively high, namely 77.9% of students are interested in entrepreneurship. Based on the Sig value (0.43 0.05), there is no significant difference between the interests of semester III, V and VII students; 3) Student self-efficacy in entrepreneurship is classified as moderate, namely only 50.6% of students believe in their abilities. Based on the Sig value (0.07 0.05), there is a significant difference between the self-efficacy of students in semesters III, V, and VII.